A phase 3, randomised, double-blind, placebo-controlled study to evaluate the efficacy and safety of erenumab in migraine prevention: primary results of the arise trial. Issue 5 (8th May 2017) - Dodick, David; Ashina, Messoud; Kudrow, David; Lanteri-Minet, Michel; Osipova, Vera; Palmer, Kerry; Picard, Hernan; Mikol, Daniel D; Lenz, Robert A
Abstract : Objectives: Efficacy and safety of erenumab, a human anti-calcitonin gene-related peptide (CGRP) receptor monoclonal antibody, were evaluated in patients with episodic migraine (EM) in a phase 3 trial (NCT02483585 ). Methods: Five-hundred and seventy seven adults with EM were randomised 1:1 to subcutaneous, monthly placebo or erenumab (70 mg). Primary endpoint was change in monthly migraine days (MMDs) from baseline to weeks 9–12 of a 12 week double-blind phase. Secondary endpoints were achievement of ≥50% reduction in MMDs, change in acute migraine-specific medication use, and ≥5-point reduction in Physical Impairment (PI) and Impact on Everyday Activities (EA) measured by the Migraine Physical Function Impact Diary. Statistical significance was determined after adjustment for multiple comparisons. Results: Patients reported a mean 8.3 MMDs at baseline. Those receiving erenumab experienced a mean −2.9 day change (reduction) from baseline in MMDs, compared with a -1.8 day reduction for placebo (p<0.001). A≥50% reduction in MMDs was achieved by 40% and 30% in erenumab and placebo groups (OR: 1.6; p=0.010). Monthly acute migraine-specific medication use was reduced by mean −1.2 and −0.6 days (p=0.002). Respective ≥5-point reductions (improvement) in PI were achieved by 33% and 27% of patients (p=0.13) and in EA by 40% and 36% (p=0.26). The safety profile of erenumab was similar to placebo. Most frequently reported AEs across both groups were upper respiratory tract infection, injection site pain and nasopharyngitis. Conclusions: Erenumab statistically significantly reduced migraine frequency, acute migraine-specific medication use and a greater proportion of patients achieved ≥50% reduction in MMDs, compared with placebo, in this phase 3 trial in EM.